Respuestas

2013-04-05T13:36:52+02:00

La suma de una P.A es:  S = [(A1 + An) / a] n;  por tanto S11 = [(A1 + A11) / a] . 11

 

S11 = 44; por tanto 44 = [(A1 + A11) /2] . 11

 

An = A1 + (n - 1) d;    A11 = A1 + (11 -1)(-2);   A11 = A1 - 20

 

Sutituyendo A11 en la fórmula de la suma:

 

44 = [ A1 + A1 -20) / 2] .11;    44 = [(2 A1 - 20) / 2] . 11 ;  quitando denominadores:

 

88 = ( 2A1 -20). 11;   88 = 22A1 - 220;   88 + 220 = 22 A1;   308 = 22 A1;   A1 = 308 / 22;    A1 = 14

 

A11 = A1 - 20;   A11 = 14 - 20;   A11 = -6